2019
DOI: 10.1093/rheumatology/kez286
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine: an emerging era of theranostics and therapeutics for rheumatoid arthritis

Abstract: RA is a multifactorial autoimmune inflammatory disease characterized by synovitis, bone destruction and joint dysfunction that leads to shortening of lifespan and increased mortality rates. Currently available treatments of RA, by controlling various symptoms, only delay disease progression and have their own side effects. Consequently, there is the need for a novel therapeutic strategy that offers a more sustainable and biocompatible solution. Nanomedicine is a modern branch of nanobiotechnology that provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Adverse events from currently available non‐selective RA treatments can be minimized by encapsulating these medicines into nanocarriers for a more precise approach to administering the medications at the intended site of action, preventing repeated or heavy dosing, increasing drug solubility and pharmacokinetics, and achieving an optimal drug concentration locally. [ 10 ] Preclinical studies have utilized nanocarriers, including dendrimers, micelles, nanoemulsions, liposomes, and nanogels, for RA treatment. However, a recently published clinical trial suggested that curcumin nanomicelles have limited benefits in patients with RA.…”
Section: Advancement Of Nanomedicine In Ra Treatmentmentioning
confidence: 99%
“…Adverse events from currently available non‐selective RA treatments can be minimized by encapsulating these medicines into nanocarriers for a more precise approach to administering the medications at the intended site of action, preventing repeated or heavy dosing, increasing drug solubility and pharmacokinetics, and achieving an optimal drug concentration locally. [ 10 ] Preclinical studies have utilized nanocarriers, including dendrimers, micelles, nanoemulsions, liposomes, and nanogels, for RA treatment. However, a recently published clinical trial suggested that curcumin nanomicelles have limited benefits in patients with RA.…”
Section: Advancement Of Nanomedicine In Ra Treatmentmentioning
confidence: 99%
“…Recent research has focused on the development of nanoparticle drug delivery systems that actively or passively target inflamed joints [7] while also improving the release of insoluble drugs, thereby maximizing bioavailability and therapeutic efficacy. Such drug delivery systems can significantly prolong drug half-life in the body and promote drug accumulation in the joints [8].…”
Section: Introductionmentioning
confidence: 99%
“…The highly innovative field of nanotheranostics has been expanding now for more than two decades, with easy-to-scale nanomaterials emerging as potential candidates to treat a variety of pathologies, such as cancer (1)(2)(3)(4), autoimmune diseases (5,6) or neurodegenerative disorders (7,8). The therapeutic interest in nanomaterials, and particularly in nanoparticles, is in part kindled by the chemical and physical versatility of these materials.…”
Section: Introductionmentioning
confidence: 99%